The state of POPs in Ghana- A review on persistent organic pollutants: Environmental and human exposure. (February 2019) - Bruce-Vanderpuije, Pennante; Megson, David; Reiner, Eric J.; Bradley, Lee; Adu-Kumi, Sam; Gardella, Joseph A.
Abstract: Ghana is one of the top pesticide users and highest persistent organic pollutant (POP) emitters in sub-saharan Africa. Despite recent increases in published data, there is limited information on how POP concentrations have changed, post ratification of the Stockholm Convention. As a result, this review aims to address these knowledge gaps by collating available data that reported POPs in Ghanaian environmental matrices, identify spatial and temporal trends, and establish potential health risks. It is worth noting that Ghana has not developed its own regulatory standards for POPs, but adapts United States Environmental Protection Agency (USEPA) standards. Results obtained showed concentrations in excess of USEPA regulatory standards for per- and poly-fluoroalkyl sulphonates (PFASs) and dichlorodiphenyldichloroethane (DDD) in water, polychlorinated and polybrominated dibenzo-p-dioxins and furans (PCDD/Fs and PBDD/Fs) in e-waste soils, and polybrominated diphenyl ethers in aquatic organisms and dairy products. The published studies do not cover major regions nationwide. The inconsistency in methods and analytes measured, along with data scarcity in some regions, makes it challenging to identify temporal trends. However, the data did indicate decreasing concentrations of some legacy POPs in soil/sediment and aquatic organisms, with increasing concentrations of some POPs in water, fish, fruits and vegetables. Studies that performed health risks assessments were limited although the data indicated risks to e-waste workers, some farmers and vulnerable sub-populations. This review identified potential human health risks from POPs in the Ghanaian environment and the need for more consistent and widespread monitoring program. Graphical abstract: Highlights: Current status of POPs in Ghana is reviewed. Health risks from PCDD/Fs at e-waste sites. High health risk from exposure to PFASs and DDT related compounds in drinking water. Large data gaps identified. Future perspectives to include understudied POPs. Abstract : This paper provides a critical review of studies of POPs in Ghana which can be used as a reference for all of Africa, as well as other developing countries, for compliance with the requirements for POPs monitoring in the e-waste, food and environmental sectors to inform the mitigation of health risks.